Country of training and ethnic origin of UK doctors: Database and survey studies (BMJ Publishing Group, 2004)
Abstract Objectives To report on the country of training and ethnicity of consultants in different specialties in the NHS, on trends in intake to UK medical schools by ethnicity, and on the specialty choices made by UK medical graduates in different ethnic groups. Design Analysis of official databases of consultants and of students accepted to study medicine; survey data about career choices made by newly qualified doctors. Setting and subjects England and Wales (consultants), United Kingdom (students and newly qualified doctors). Results Of consultants appointed before 1992, 15% had trained abroad; of those appointed in 1992-2001, 24% had trained abroad. The percentage of consultants who had trained abroad and were non-white was significantly high, compared with their overall percentage among consultants, in geriatric medicine, genitourinary medicine, paediatrics, old age psychiatry, and learning disability. UK trained non-white doctors had specialty destinations similar to those of UK trained white doctors. The percentage of UK medical graduates who are non-white has increased substantially from about 2% in 1974 and will approach 30% by 2005. White men now comprise little more than a quarter of all UK medical students. White and non-white UK graduates make similar choices of specialty. Conclusions Specialist medical practice in the NHS has been heavily dependent on doctors who have trained abroad, particularly in specialties where posts have been hard to fill. By contrast, UK trained doctors from ethnic minorities are not over-represented in the less popular specialties. Ethnic minorities are well represented in UK medical school intakes; and white men, but not white women, are now substantially under-represented.